Comparative study of scientific literacy: Indonesian and Thai pre-service science teachers report - R. Ahmad Zaky El Islami; Prasart Nuangchalerm (International Journal of Evaluation and Research in Education (IJERE), 2020)
The changing world needs literate citizens to live with creative society. This study aimed to compare science literacy of novice science teacher students from Thailand and Indonesia. Panel participants were 95 of Thai and 71 of Indonesian novice science teacher students who have been studying in the 1st and 2nd year of study in bachelor degree of science education programme. Data were collected by employed science literacy inventory; it was used for asking four components: content of science, context of science, science process, and scientific attitude based on local wisdom of Baduy’s society. Participants are freely considered in their perception. Results showed that Thai novice science teacher students had slightly better score than those Indonesian novice science teacher students, but statistical testing is not showed the differences. The future study is required to more investigation of how they promote science literacy in their school practicum.